Richard Lionheart dan Shalahuddin Al Ayyubi dalam Perebutan Kota Suci Yerusalem - Syaelendra, Rangga; Suwirta, Andi; Darmawan, Wawan (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This study discusses the strategy and pattern of battle carried out by Richard Lionheart, the leader of the Western nations, and Shalahuddin Al-Ayyubi, the leader of the Arabs. This research uses a historical method consisting of four steps: heuristics, criticism, interpretation, and historiography. This research also uses a multidisciplinary approach by taking the concepts of war, leadership, and the holy city to discuss the research themes raised. Based on the study’s results, Richard Lionheart and Shalahuddin Al-Ayyubi had different journeys in their background, occupying positions that made them leaders of two different nations, where Richard Lionheart became King of British. In contrast, Shalahuddin Al-Ayyubi became the nation’s king. Richard Lionheart and Shalahuddin Al-Ayyubi also have strategies and patterns of fighting that are different from one another, with their advantages and disadvantages giving each of them an advantage over their opponents. Besides that, the two nation’s leaders fighting over the Holy City of Jerusalem has the same importance to the Holy City of Jerusalem; for both the leaders of this nation, both Western and Arab nations, Jerusalem is a city that not only has a religious relationship for these two nations, which in addition to having the religious ties, the two nations also had the same historical ties in the past to this Holy City of Jerusalem. These two nations feel they have the same rights in the Holy City of Jerusalem.